Rancang Bangun Aplikasi Pengenalan Ukiran Bali dengan Metode ORB - Sumantara, I Gusti Lanang Trisna; Bayupati, I Putu Agung; Wirdiani, Ni Kadek Ayu (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2017)
Balinese carving is one of the arts and culture in Bali and have various types in its application, but the lack of information resulted in people do not really know the kinds of Balinese carving. Lack of information about Balinese carvings can be solved by utilizing advances in information technology in image processing, which is to make application that can recognize Balinese carvings. Applications that made is a mobile application that can be used on smartphones with Android operating system. The method that applied is Oriented FAST and Rotated BRIEF (ORB) that able to recognize the image of Bali carving based on the features keypoints. Carved image matching using Bruteforce Hamming Distance to find the similarity between features carved images so that they can be identified. The results of the accuracy of the research process recognition Balinese carving method ORB reaches the percentage of 48% Balinese carvings recognizable and 52% did not recognize, so it can be concluded the result method ORB is quite good to recognize Balinese carving.